An acceptance and commitment therapy group intervention for university women survivors of intimate partner violence in Turkey: A pilot feasibility study - Bektas-Aydin, Ceren; Yuksel-Sahin, Fulya (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
The purpose of the study was to evaluate the feasibility of a 10-sessions group intervention program based on Acceptance and Commitment Therapy, prepared for female university students who experienced intimate partner violence (IPV) in Turkey. The study sample consisted of eight Turkish IPV survivor university women. Participant adherence, implementation, acceptability, and preliminary evidence of benefit were measured within the scope of the feasibility. The outcome measures for preliminary evidence of benefit were post-traumatic stress symptoms (PTS), psychological inflexibility (PI), and self-compassion (SC). The program completion and retention rates revealed the high participant adherence. The sessions were conducted as planned, and the content was found to be feasible for implementation in a group setting. The average score given to each question on the Program Evaluation Form was above eight out of 10, indicating that the program was considered highly acceptable. The results of ANOVA analysis showed that the mean PTS, PI, and SC scores differed significantly across three-time points (pretest, posttest, one-month follow up) with large effect sizes. It was observed that there was a significant decrease in PTS and PI, while there was a significant increase in SC among the participants at the end of the ACT-based group intervention. The improvements in all three outcomes remained significant at the one-month follow-up. In conclusion, the results indicated that the group-based ACT intervention for IPV survivor university women was feasible and could be effective in addressing post-traumatic stress, psychological inflexibility, and self-compassion.
Keywords: Intimate partner violence; University women; Acceptance and commitment therapy; Psychological inflexibility; Self-compassion; Post-traumatic stress; Group intervention; TACTICS-SCALES CTS2; VICTIMIZATION; DISORDERS; TRAUMA; METAANALYSIS; FLEXIBILITY; VALIDITY; ANXIETY; Women's Studies